A serious game-based solution to prevent bullying. Issue 2 (6th June 2016) - Raminhos, Cátia; Cláudio, Ana Paula; Carmo, Maria Beatriz; Gaspar, Augusta; Carvalhosa, Susana; Candeias, Maria de Jesus
Abstract : Purpose: The purpose of this paper is to present a Serious Game with the main purpose of inducing attitude changes as a way to prevent bullying, in a target audience of young people between 10 and 12 years old. Design/methodology/approach: The rationale for prevention is: first, to help victims of these aggressive episodes to acquire or improve competencies in avoiding or dealing with future real bullying situations; and second, to promote empathy toward the victims in bystanders. A back office application complements the game, providing substantial assistance to psychologists while using the game with patients in therapy or in research work. Findings: Both components, the game and the back office, were evaluated with volunteers. The user study leads the authors to the conclusion that the current version of the game holds good potential in bullying prevention: the young people that played the game in a continuous time span, at the end of this testing process, have expressed improvements in their bullying prevention strategies. The back office application, a distinctive feature of the solution when compared to other similar bullying prevention solutions, was positively assessed by the psychologists who tested it. Originality/value: The game deals with strong social features, such as number of friends and invitations to social events (e.g. a birthday party), to which young people give much importance. Additionally, it offers a variability of scenarios and consequences of actions, taking into account the user's performance in the game. The main factors that makes the presented solution stand out in comparison with other similar bullying prevention solutions are mainly the following: It includes a back office application to assist therapists with data management features; the role of the player in the game can be chosen according to his own profile; it is possible to play even outside a therapy session (e.g. at home); and it is a portable solution.